STRATEGI KEPALA SEKOLAH DALAM MEWUJUDKAN PROFIL PELAJAR PANCASILA DIMENSI BERIMAN DAN BERTAKWA UNTUK PENINGKATAN MUTU PENDIDIKAN DI SEKOLAH DASAR - Listiyani, Laikha; Fitri Puji Rahmawati; Anik Ghufron (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research aims to explore in-depth the strategies employed by the school principal in developing Pancasila students who are faithful and pious at SDN 01 Karanganyar, and how these strategies contribute to improving educational quality. This study uses a qualitative approach designed as a case study. The subjects of the research include the principal, teachers, and students of SDN 01 Karanganyar. Data collection techniques consist of observation, interviews, and documentation. To enhance the validity and reliability of the research, data triangulation was conducted. The results show that the structured and contextual strategies implemented at SDN 01 Karanganyar successfully created Pancasila students who are faithful, pious, and of noble character. The implementation of the teacher’s affection strategy in religious activities demonstrated a significant improvement in students’ religious habits and character.